Phenotypical Changes of Hematopoietic Stem and Progenitor Cells in Sepsis Patients: Correlation With Immune Status? - Ping Wang; Jun Wang; Yi-hao Li; Lan Wang; Hong-cai Shang; Jian-xun Wang (Frontiers Media S.A., 2021)
Background: Sepsis is life-threatening organ dysfunction associated with high risk of death. The immune response of sepsis is complex and varies over time. The immune cells are derived from hematopoietic stem and progenitor cells (HSPCs) which can respond to many infections. Our previous study found that sepsis causes HSPC dysregulation in mouse. But few studies have previously investigated the kinetics of HSPC and its contribution to immune system in sepsis patients.Purpose: We aimed to identify the kinetics of HSPCs and their contribution to immune system in sepsis patients.Methods: We enrolled eight sepsis patients and five healthy control subjects. Peripheral blood (PB) samples from each patient were collected three times: on the first, fourth, and seventh days, once from each healthy control subject. Peripheral blood mononuclear cells (PBMCs) were isolated by density centrifugation and stained with cocktails of antibodies. Populations of HSPCs and their subpopulation were analyzed by flow cytometry. Immune cells were characterized by flow cytometry and blood cell analysis. Correlations between HSPCs and immune cells were analyzed using the Pearson correlation test.Results: We found that the frequency of HSPCs (CD34+ cells and CD34+CD38+ cells) in sepsis patients on day 4 was significantly higher than that in the healthy controls. The most pronounced change in subpopulation analysis is the frequency of common myeloid progenitors (CMPs; CD34+CD38+CD135+CD45RA−). But no difference in the immunophenotypically defined hematopoietic stem cells (HSCs; CD34+CD38−CD90+CD45RA−) in sepsis patients was observed due to rare HSC numbers in PB. The number of PBMCs and lymphocytes are decreased, whereas the white blood cell (WBC) and neutrophil counts were increased in sepsis patients. Importantly, we found a negative correlation between CD34+ on day 1 and WBC and lymphocytes on day 4 from correlation analysis in sepsis patients.Conclusion: The present study demonstrated that the HSPC and its subpopulation in sepsis patients expanded. Importantly, the changes in HSPCs at early time points in sepsis patients have negative correlations with later immune cells. Our results may provide a novel diagnostic indicator and a new therapeutic approach.